1991
DOI: 10.1177/014362449101200401
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thermal models: Reliability for domestic building design

Abstract: This paper describes a three year UK initiative—Applicability Study 1-to enhance the usability and credibility of detailed thermal simulation programs with particular reference. to the design of passive solar dwellings. Researchers at Leicester Polytechnic and the Building Research Establishment are working with ESP, HTB2 and SERIRES. The aims are to identify the problems for which these programs can be used reliably and those for which they cannot, to provide guidance on the best modelling techniques, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…5 Some of this collaborative research effort has been reported in this Journal. 6,7 Getting reliable results from simulation tools requires skilled users. Given the large quantity of parameter data that the user has to select in building a model, the process is somewhat error prone.…”
Section: The State Of Building Energy Simulationmentioning
confidence: 99%
“…5 Some of this collaborative research effort has been reported in this Journal. 6,7 Getting reliable results from simulation tools requires skilled users. Given the large quantity of parameter data that the user has to select in building a model, the process is somewhat error prone.…”
Section: The State Of Building Energy Simulationmentioning
confidence: 99%
“…Inter-model comparison work involving BREDEM and more detailed, dynamic thermal models, can be found elsewhere. 9,10…”
Section: Introductionmentioning
confidence: 99%